Statistical convergence and strong p-Cesàro summability of order ? in sequences of fuzzy numbers - Altinok, H.; Altin, Y.; Işik, M. (My University, 2012)
In this study we introduce the concepts of statistical convergence of order ? and strong p-Cesàro summability of order ? for sequences of fuzzy numbers. Also, we give some relations between the statistical convergence of order ? and strong p-Cesàro summability of order ? and construct some interesting examples.
Keywords: Cesro summability; Fuzzy number; Statistical convergence